Person‐Centered Care: Opportunities and Challenges for Academic Dental Institutions and Programs. Issue 11 (1st November 2017) - Walji, Muhammad F.; Karimbux, Nadeem Y.; Spielman, Andrew I.
Abstract : Many readers may be familiar with patient ‐centered care, but they may not be familiar with the concept of person ‐centered care. Person‐centered care implies knowing the patient as a person, not as just another patient or as a clinical requirement in dental school. Person‐centered care gains the trust of the patient and is meaningful to the person because it respects his or her values, preferences, needs, and beliefs, emphasizing the individual's freedom of choice while promoting emotional and physical comfort. This article describes the concept of person‐centered care, compares person‐centered care with patient‐ and student‐centered care, presents a vision of person‐centered care in a clinic setting, discusses its opportunities and challenges in general, and outlines future topics of interest for the academic, research, and practicing dental communities, including opportunities for in‐depth reviews and guidelines.